Managerial implications on the relation of digital leadership, digital culture, organizational learning, and innovation of the employee performance (case study of PT. Telkom digital and next business department) - Muniroh, Muniroh; Hamidah, Hamidah; Abdullah, Thamrin (Management and Entrepreneurship: Trends of Development, 2022)
PT. Telkom Digital and Next Business Department is a supporting institution in PT Telkom Indonesia, one of the State-Owned Enterprises (BUMN) engaged in the telecommunications and information industry. Since the world has experienced broad cultural, social, and economic changes based on increasing digital technology, reliable resources are needed regarding employee performance. This study aims to analyze the influence of digital leadership, digital culture, organizational learning, innovation on employee performance at PT. Telkom Digital Next Business Department. This study uses a quantitative approach with the Partial Least Square (PLS) technique with one of the alternative methods of Structural Equation Modeling (SEM). The research sample is the employees of PT. Telkom Digital and Next Business Department, totaling 160 employees with a population of 306 employees located in Jakarta and Bandung. Empirically the research results show that digital leadership does not directly affect employee performance, digital culture does not directly affect employee performance, organizational learning does not directly affect employee performance, and innovation has a direct positive effect on employee performance. Furthermore, Digital Leadership has a direct positive effect on Innovation, then Digital Culture does not directly affect Innovation, Organizational learning has a direct positive effect on innovation. The final result of this research is to obtain Managerial Implications and Recommendations for PT. Telkom Digital Next Business Department is very necessary for the development of aspects of Digital Leadership, Digital Culture, Organizational Learning, and Employee Performance in improving Innovation that affects Employee Performance PT. Telkom Digital Next Business Department.JEL Classification: M1, M21, M2